High serotonin levels during brain development alter the structural input-output connectivity of neural networks in the rat somatosensory layer IV - Miceli, Stéphanie; Negwer, Moritz; van Eijs, Fenneke; Kalkhoven, Carla; van Lierop, Ilja; Homberg, Judith; Schubert, Dirk (Frontiers in Cellular Neuroscience, 2013)
Homeostatic regulation of serotonin (5-HT) concentration is critical for “normal” topographical organization and development of thalamocortical (TC) afferent circuits. Down-regulation of the serotonin transporter (SERT) and the consequent impaired reuptake of 5-HT at the synapse, results in a reduced terminal branching of developing TC afferents within the primary somatosensory cortex (S1). Despite the presence of multiple genetic models, the effect of high extracellular 5-HT levels on the structure and function of developing intracortical neural networks is far from being understood. Here, using juvenile SERT knockout (SERT-/-) rats we investigated, in vitro, the effect of increased 5-HT levels on the structural organization of (i) the thalamocortical projections of the ventroposteromedial thalamic nucleus towards S1, (ii) the general barrel-field pattern and (iii) the electrophysiological and morphological properties of the excitatory cell population in layer IV of S1 (spiny stellate and pyramidal cells). Our results confirmed previous findings that high levels of 5-HT during development lead to a reduction of the topographical precision of TCA projections towards the barrel cortex. Also, the barrel pattern was altered but not abolished in SERT-/- rats. In layer IV, both excitatory spiny stellate and pyramidal cells showed a significantly reduced intracolumnar organization of their axonal projections. In addition, the layer IV spiny stellate cells gave rise to a prominent projection towards the infragranular layer Vb. Our findings point to a structural and functional reorganization, of TCAs, as well as early stage intracortical microcircuitry, following the disruption of 5-HT reuptake during critical developmental periods. The increased projection pattern of the layer IV neurons suggests that the intracortical network changes are not limited to the main entry layer IV but may also affect the subsequent stages of the canonical circuits of the barrel cortex.